The utility and prognostic value of dipyridamole technetium-99m sestamibi myocardial perfusion imaging SPECT in predicting perioperative cardiac events following non-cardiac surgery. (July 2013) - Asli, IN; Shahoseini, R; Azizmohammadi, Z; Javadi, H; Assadi, M
Objective: A perioperative cardiac events is one of the most important medical concerns for both surgeons and patients. The purpose of the current study was to determine the prognostic value of myocardial perfusion imaging (MPI), using dipyridamole 99m Tc-MIBI, for the prediction of perioperative cardiac events. Materials and methods: This study included 253 patients who were candidates for non-cardiac elective surgery and underwent scanning with dipyridamole 99m Tc-MIBI. Based on normal or abnormal MPI, patients were divided into two groups and all preoperative cardiac events were recorded. Risk factors, including diabetes mellitus, dyslipidemia, hypertension, smoking and age ≥70 years, were compared between patients with normal and abnormal MPI and, also, in patients with or without cardiac events. Results: There were 197 patients with normal and 56 patients with abnormal MPI. In total, 14 patients had perioperative cardiac events, which included myocardial infarction (MI), hypotension, arrhythmia and death; of the 14 patients with perioperative cardiac events, 12 had abnormal and two had normal MPI. There were statistically meaningful differences between the two groups (p<0.001). Based on these findings, we determined that MPI had a sensitivity of 85.7%, a specificity of 81.6%, an accuracy of 81.8%, a positive predictive value of 21.4 % and a negative predictive value of 98.9%. Conclusion: The incidence of perioperative cardiac events is higher in patients with abnormal MPI. Dipyridamole 99m Tc-MIBI myocardial perfusion imaging can accurately detect the preoperative cardiac risk of patients undergoing major non-cardiac surgery. Based on these findings, the occurrence of perioperative cardiac events in patients with abnormal MPI should be considered, especially in the older age population (age ≥70).